Golden Ratio Geometry and the Fine-Structure Constant - Sherbon, Michael A. (JOURNAL OF ADVANCES IN PHYSICS, 2019)
The golden ratio is found to be related to the fine-structure constant, which determines the strength of the electromagnetic interaction. The golden ratio and classical harmonic proportions with quartic equations give an approximate value for the inverse fine-structure constant the same as that discovered previously in the geometry of the hydrogen atom. With the former golden ratio results, relationships are also shown between the four fundamental forces of nature: electromagnetism, the weak force, the strong force, and the force of gravitation.